Ð¡Ð¾Ð´ÐµÑ€Ð¶Ð°Ð½Ð¸Ðµ Ñ†Ð¸Ñ‚Ð¾ÐºÐ¸Ð½Ð¾Ð² Ð² ÑÑ‹Ð²Ð¾Ñ€Ð¾Ñ‚ÐºÐµ ÐºÑ€Ð¾Ð²Ð¸ Ð¿Ð¾ÑÐ»Ðµ Ñ€Ð¸Ñ‚Ð¼Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ñ‹Ñ… Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ð¹ - Babijchuk, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
As the result of the researches the significant deviations towards the rise of pro-inflammatory cytokines in content of aged people’s blood serum have been revealed. Rhythmic cold effects strongly reduce the content of pro-inflammatory interleukins in blood serum down to normal values in middle-aged and aged people and increase the content of granulocyte colony-forming factor (GCFF), that testifies to stimulating effect of low temperatures on adaptive abilities of immune system and, in particular, of its humoral link.